2007
DOI: 10.1017/s0025315407055002
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the distribution of Cuvier's beaked whale (Ziphius cavirostris) in relation to topographic features in the Pelagos Sanctuary (north-western Mediterranean Sea)

Abstract: Cuvier's beaked whale is a poorly-known species. It has been considered common since 1980 in the Pelagos Sanctuary (north-western Mediterranean Sea), but it has hardly been studied, chiefly due to difficulties in sighting. Stranding data indicates that the beaked whale is present all along the Ligurian coast. As with any deep-diving odontocete, Cuvier's beaked whale feeds mostly on deep-sea squid, but also on some fish and a small number of crustaceans. As a consequence, it is thought to be found mainly in wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 19 publications
4
41
2
Order By: Relevance
“…In the Pelagos Sanctuary, Cuvier's beaked whale exploits the upper and lower slopes along the Ligurian−Provençal coast, at depths ranging from 1000 to 2500 m (Azzellino et al 2008, Moulins et al 2008, showing preference for areas with complex topography (Moulins et al 2007, Gannier & Epinat 2008, Azzellino et al 2012. Similar habitat preferences have been found for the sperm whale, whose preferred habitat lies in the canyons in the slope area (Gannier et al 2002, Moulins et al 2008, Praca et al 2009, Azzellino et al 2012.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…In the Pelagos Sanctuary, Cuvier's beaked whale exploits the upper and lower slopes along the Ligurian−Provençal coast, at depths ranging from 1000 to 2500 m (Azzellino et al 2008, Moulins et al 2008, showing preference for areas with complex topography (Moulins et al 2007, Gannier & Epinat 2008, Azzellino et al 2012. Similar habitat preferences have been found for the sperm whale, whose preferred habitat lies in the canyons in the slope area (Gannier et al 2002, Moulins et al 2008, Praca et al 2009, Azzellino et al 2012.…”
Section: Introductionmentioning
confidence: 53%
“…Many studies demonstrate how these datasets, when collected following an ad hoc protocol and/or analyzed taking into account potential sources of bias, can be a valuable resource for understanding species distribution. Whalewatching data sets have previously been used to characterize ceta cean habitats within the Pelagos Sanc tuary (Azzellino et al 2001, 2008, Moulins et al 2007.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All cetaceans regularly observed in the Mediterranean Sea, including seven species of odontocetes (Cuvier's beaked whale (Z. cavirostris), striped dolphin (Stenella coeruleoalba), Risso's dolphin (Grampus griseus), sperm whale (Physeter macrocephalus), long-finned pilot whale (Globicephala melas), common bottlenose dolphin (Tursiops truncatus), shortbeaked common dolphin (Delphinus delphis)) and only one species of mysticete, the fin whale (Balaenoptera physalus) are found in this region. The Gulf of Genoa in the Ligurian Sea was found to be a key area in the western Mediterranean Basin since Cuvier's beaked whales have been regularly observed at sea (Azzellino et al, 2008;D'Amico et al, 2003;Macleod and Mitchell, 2006;Moulins et al, 2007). The Gulf of Genoa is characterized by several canyons with very steep slope gradients extending from the shelf break to a depth of about 1200 m. The Genoa canyon region (Fig.…”
Section: Model Development Areamentioning
confidence: 99%
“…Several studies have, in fact, reported beaked whales as regularly observed over the continental slope in waters 200-2000 m depth, (Hamazaky, 2002;Hooker et al, 2002;MacLeod and Zuur, 2005;Waring et al, 2001) and near submarine canyons (Wimmer and Whitehead, 2004). In the Mediterranean Sea, Cuvier's beaked whale presence has been found associated with the continental slope area and submarine canyons (Azzellino et al, 2008;Cañadas et al,2002;D'Amico et al, 2003;Gannier and Epinat, 2008;Moulins et al, 2007). This was another reason for trying a ''validation'' exercise using bathymetry as predictor for this species.…”
Section: Observed Correct Predictionsmentioning
confidence: 99%